2011
DOI: 10.1037/a0021815
|View full text |Cite
|
Sign up to set email alerts
|

Parental criticism and externalizing behavior problems in adolescents: The role of environment and genotype–environment correlation.

Abstract: Genetic factors are important for the association between parental negativity and child problem behavior, but it is not clear whether this is dueto passive or evocative genotype-environment correlation (rGE). In this study we applied the extended children-of-twins model to directly examine the presence of passive and evocative rGE as well as direct environmental effects in the association between parental criticism and adolescent externalizing problem behavior. The cross-sectional data come from the Twin and O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 67 publications
(122 reference statements)
4
90
0
2
Order By: Relevance
“…Because we examined biological families, we cannot rule-out the possibility that shared genes may account for what appears to be an environmental association. That said, existing empirical literature (Marceau et al, 2013; Narusyte et al, 2011b) has not identified passive rGE effects in the association between parenting and child antisocial behavior, implying that passive rGE is unlikely account for the association between parenting and offspring behavior problems in this study. Building on these results, several adoption studies have found evidence of a shared environmentally-driven association between parenting and antisocial behavior in general (Burt et al, 2007; Klahr et al, 2011a, 2011b), results that again argue against passive rGE (because passive rGE is entirely circumvented in non-biologically related family members).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Because we examined biological families, we cannot rule-out the possibility that shared genes may account for what appears to be an environmental association. That said, existing empirical literature (Marceau et al, 2013; Narusyte et al, 2011b) has not identified passive rGE effects in the association between parenting and child antisocial behavior, implying that passive rGE is unlikely account for the association between parenting and offspring behavior problems in this study. Building on these results, several adoption studies have found evidence of a shared environmentally-driven association between parenting and antisocial behavior in general (Burt et al, 2007; Klahr et al, 2011a, 2011b), results that again argue against passive rGE (because passive rGE is entirely circumvented in non-biologically related family members).…”
Section: Discussionmentioning
confidence: 66%
“…Importantly, however, this study examined overall family functioning rather than parenting; it is thus unclear whether these findings apply to parenting more specifically. Indeed, available studies examining this question indicate that the effects of passive rGE on the association between parenting and child antisocial behavior are small to non-existent (Harold et al, 2013; Marceau et al, 2013; Narusyte et al, 2011b). For example, Marceau and colleagues (2013) modeled passive rGE effects (along with evocative rGE and environmental pathways) underlying the association between negative parenting and adolescent externalizing problems using the Extended Children of Twins model (Narusyte et al, 2008).…”
Section: Pathway 2: Genetic Mediationmentioning
confidence: 99%
See 2 more Smart Citations
“…The link between maternal criticism and adolescent problem behavior was explained by reactive rGE whereas paternal criticism was not. Paternal criticism did not occur in response to adolescent problem behavior, but rather directly affected it through environmental pathways (Narusyte et al 2011). However, more recent work has suggested that reactive rGE, although pervasive in adolescence and young adulthood, may dissipate in adulthood.…”
Section: Behavior Genetics and Parenting Influences In Adolescencementioning
confidence: 99%